Cyclic Solid‐State Multiple Phase Changes with Tuned Photoemission in a Gold Thiolate Coordination Polymer. Issue 14 (16th February 2022) - Veselska, Oleksandra; Vaidya, Shefali; Das, Chinmoy; Guillou, Nathalie; Bordet, Pierre; Fateeva, Alexandra; Toche, François; Chiriac, Rodica; Ledoux, Gilles; Wuttke, Stefan; Horike, Satoshi; Demessence, Aude
Abstract: The discovery of a universal memory that exhibits fast access speed, high‐density storage, and non‐volatility has fuelled research into phase‐change materials over the past decades. In spite of the efficiency of the inorganic chalcogenides for phase‐change random access memory (PCRAM), they still have some inherent drawbacks, such as high temperature required for phase change and difficulty to control the domain size of the phase change, because of their brittleness. Here we present a Au I –thiolate coordination polymer which undergoes two successive phase changes on application of mild heating (<200 °C) from amorphous‐to‐crystalline1‐to‐crystalline2 phases. These transitions are reversible upon soft hand grinding. More importantly, each phase exhibits different photoluminescent properties for an efficient optical read‐out. We believe that the ability of the Au I –thiolate coordination polymer to have reversible phase changes under soft conditions and at the same time to display distinct optical signals, can pave the way for the next generation of PCRAM. Abstract : A non‐emissive amorphous Au I –thiolate coordination polymer undergoes two successive crystallisation phase changes on mild solid‐state heating. The first high symmetric crystalline phase becomes slightly red‐emissive and the second, which has a lower symmetry, exhibits intense luminescence due to the presence of aurophilic interactions. These transitions are reversible upon soft hand grinding, offering potential for non‐volatile memories.